2023
DOI: 10.3389/fphar.2023.1196783
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine-induced Retinal Toxicity

Abstract: Long-term use of hydroxychloroquine can cause retinopathy, which may result in severe and progressive visual loss. In the past decade, hydroxychloroquine use has markedly increased and modern retinal imaging techniques have enabled the detection of early, pre-symptomatic disease. As a consequence, the prevalence of retinal toxicity in long-term hydroxychloroquine users is known to be higher than was previously estimated. The pathophysiology of the retinopathy is incompletely characterised, although significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 185 publications
0
9
0
Order By: Relevance
“…Modern imaging allows for more objective classification of retinopathy by severity and pattern, but variations in the interpretation of these tests still contribute to inconsistencies in toxicity definitions. 34 Allahdina et al proposed a new staging system based on OCT findings: stage 1 includes minor changes limited to the parafoveal region; stage 2 includes clear localised changes in the parafoveal region; stage 3 includes extensive parafoveal changes; and stage 4 includes foveal involvement. While this system is primarily applicable to eyes with parafoveal retinopathy, these stages have been functionally related to visual acuity, visual field test results or mfERG and are significantly associated with the degree of further progression.…”
Section: Discussionmentioning
confidence: 99%
“…Modern imaging allows for more objective classification of retinopathy by severity and pattern, but variations in the interpretation of these tests still contribute to inconsistencies in toxicity definitions. 34 Allahdina et al proposed a new staging system based on OCT findings: stage 1 includes minor changes limited to the parafoveal region; stage 2 includes clear localised changes in the parafoveal region; stage 3 includes extensive parafoveal changes; and stage 4 includes foveal involvement. While this system is primarily applicable to eyes with parafoveal retinopathy, these stages have been functionally related to visual acuity, visual field test results or mfERG and are significantly associated with the degree of further progression.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of antiendothelial antibodies in systemic lupus erythematosus, complement-mediated cytotoxicity causes vascular endothelial cell damage, resulting in microvascular dysfunction that can affect blood vessels anywhere in the body [10]. Although HCQ has a favorable safety pro le as a rst-line agent for SLE at present, current studies have shown that 7.5 percent of all patients taking the drug long-term have retinopathy, and its prevalence increases with the duration of treatment and the increase in the dose per kilogram of body weight [11,12].…”
Section: Dissussionmentioning
confidence: 99%
“…It has immunomodulatory actions that reduce inflammation and immune activation [ 3 ]. The anti-inflammatory effect is likely due to a decrease in cytokine production through alteration of transcription, specifically interleukins IL-6 and IL1β [ 4 ]. In patients with lupus, hydroxychloroquine therapy reduces organ damage, the risk of infection, and the risk of thrombosis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors include age over 60 years old, kidney or liver disease, or an existing retinal disease [ 1 ]. Hydroxychloroquine retinopathy is typically described as bull’s eye maculopathy caused by parafoveal mottling of the retinal pigment epithelium (RPE) [ 4 ]. On optical coherence tomography (OCT) imaging, loss of photoreceptor layers beginning in the ellipsoid zone may be seen [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation